PENINGKATAN LITERASI DAN MUTU PENDIDIKAN BAGI MASYARAKAT DESA SUKARAGAM - Indriyani, Liya; Rizki Gunawan, Akmal; Marginingsih, Ria (Universitas Islam 45 Bekasi, 2024)
The problems that occur in Sukaragam Village, Serang Baru Subdistrict, namely the lack of children's books or lessons that make their interest in reading and basic education decrease and the lack of parental knowledge of how to distinguish true and false information or news. Thus, the implementation of community service in the programme to improve literacy and the quality of education for elementary school children in Sukaragam Village. The community service method applies community education in the form of socialisation in the form of seminars. The success of this activity is to contribute to improving the overall quality of life of the people of Sukaragam Village. With increased literacy and quality of education, the community will have better access to information, opportunities, and resources that can improve the welfare and quality of life of the community.